Mapping a Magnetic Superstorm: March 1989 Geoelectric Hazards and Impacts on United States Power Systems. Issue 5 (26th May 2022) - Love, Jeffrey J.; Lucas, Greg M.; Rigler, E. Joshua; Murphy, Benjamin S.; Kelbert, Anna; Bedrosian, Paul A.
Abstract: A study is made of the relations between geomagnetic and geoelectric field variation, Earth‐surface impedance, and operational interference ("anomalies") experienced on electric‐power systems across the contiguous United States during the 13–14 March, 1989, magnetic storm. For this, a 1‐min‐resolution sequence of geomagnetic field maps is constructed from magnetometer time series acquired at ground‐based observatories. Induced geoelectric field maps are calculated by convolving the geomagnetic maps with magnetotelluric impedance tensors. During the storm, anomalies were concentrated where the lithosphere is electrically resistive, and when and where geoelectric field amplitudes were high. This was particularly true in the Mid‐Atlantic, Northeast, and the upper Midwest. Few anomalies were experienced in other parts of the Midwest and across much of the West, where the lithosphere is more conductive, and when and where geoelectric field amplitudes were low. Peak 1‐min‐resolution geoelectric field amplitude ranged from 21.66 V/km in Maine and 19.02 V/km in Virginia to <0.02 V/km in Idaho. Latitude‐dependent organization of geoelectric hazards by auroral‐zone electrojet currents is detectable, but it is much weaker than geographic organization due to surface impedance. Hazardous geoelectric fields were induced during different storm phases, at different local times, and, by inference, by a variety of ionospheric currents. Compared to geoelectric field amplitudes realized across the United States during March 1989, hazard maps used by utility companies to estimate systems exposure have much less geographic detail and a much smaller maximum‐to‐minimum range in geoelectric field amplitude. Future research would benefit from denser geomagnetic monitoring, additional magnetotelluric surveying, and access to power‐system impact data. Plain Language Summary: Electric fields induced in the Earth during magnetic storms can drive uncontrolled currents in electric‐power systems, interfering with their operation. Geomagnetically induced currents realized during the magnetic storm of March 1989 caused a blackout in Québec, Canada, and, in the Mid‐Atlantic and Northeast United States, they caused operational interference for electric‐power companies and damaged a high‐voltage transformer. In support of projects for estimating geoelectric hazards and improving power‐system resilience, maps are made of March 1989 magnetic‐storm geoelectric hazards and corresponding impacts on United States power systems. Results are based on modeling geomagnetic monitoring data, geoelectromagnetic survey data, and a compilation of published reports of power‐system interference. During the storm, electric‐power system interference was concentrated where the lithosphere is relatively electrically resistive, and when and where the geoelectric field was of high amplitude. This was particularly true in the Mid‐Atlantic and Northeast, near many of America's largest cities, and in the upper Midwest. Retrospective analyses, such as this one for the March 1989 storm, show where utility companies might concentrate their efforts to mitigate the impacts of future magnetic superstorms. Key Points: Electric‐power system interference was concentrated where surface impedance is high, and when and where geoelectric field amplitudes were high High geoelectric hazards and numerous power‐system anomalies were realized in the Eastern United States, near many large cities Power‐system impact data provide important, if partial, validation of retrospectively constructed geoelectric field maps